Behavioral and transcriptome alterations in male and female mice with postnatal deletion of TrkB in dorsal striatal medium spiny neurons - Unterwald, Ellen M (BioMed Central, 2013)
BACKGROUND: The high affinity tyrosine kinase receptor, TrkB, is the primary receptor for brain derived neurotrophic factor (BDNF) and plays an important role in development, maintenance and plasticity of the striatal output medium size spiny neuron. The striatal BDNF/TrkB system is thereby implicated in many physiologic and pathophysiologic processes, the latter including mood disorders, addiction, and Huntington’s disease. We crossed a mouse harboring a transgene directing cre-recombinase expression primarily to postnatal, dorsal striatal medium spiny neurons, to a mouse containing a floxed TrkB allele (fB) mouse designed for deletion of TrkB to determine its role in the adult striatum. RESULTS: We found that there were sexually dimorphic alterations in behaviors in response to stressful situations and drugs of abuse. Significant sex and/or genotype differences were found in the forced swim test of depression-like behaviors, anxiety-like behaviors on the elevated plus maze, and cocaine conditioned reward. Microarray analysis of dorsal striatum revealed significant dysregulation in individual and groups of genes that may contribute to the observed behavioral responses and in some cases, represent previously unidentified downstream targets of TrkB. CONCLUSIONS: The data point to a set of behaviors and changes in gene expression following postnatal deletion of TrkB in the dorsal striatum distinct from those in other brain regions.